Shariah compliance risk management in the provision of wakaf-zakat housings - Puteri Nur Farah Naadia M.F.,; Khairuddin Abdul Rashid, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The presence of risks in development of wakaf-zakat housings, as in other developments, are inevitable. The risks if it is not managed properly may cause loss and damages to properties. Consequently, a proper management of risks is crucial in order to mitigate risks. However, the management of risk in the provision of wakaf-zakat housings, as stated in manual guidelines published by JAWHAR (2009; 2007) seems inadequate as it focuses only on the protection of wakaf and zakat properties. Due to the inadequacy, in particular to benefit the asnafi and needy, loss and damages occur upon occurrence of risks probably are due to syubhah methodology adopted in managing risks. Consequently, a study is conducted to review literature on the practice of conventional and Shariah compliance risk management leading to a synthesis framework that could then be recommended for adoption for Shariah compliance risk management in the provision of wakaf-zakat housings. The study is an extended research on the protection of wakaf-zakat properties for the needy and poor via takaful. The study combines review of literature and intensive discussions with experts specializing in the Shariah, wakaf and zakat, and practitioners i.e. developers and consultants involved in wakaf-zakat housings and their contents projects. Findings of the study suggest that: Shariah compliance risk management in the provision of wakaf-zakat housings are not being practiced; the practice lack comprehensiveness in terms of the management of risks in the provision of wakaf-zakat housings, and; the outcome of the study is a synthesis list comprising of processes and steps in Shariah compliance risk management in the provision of wakaf-zakat housings is produced.